PEMBERDAYAAN MASYARAKAT MELALUI EXPERIENTIAL ECOTOURISM BERBASIS ABCD DI DESA SIGEDANG, WONOSOBO - Jumiati Ningsih; Rafly Satria; Nadina Nazwa Dwiningtias; Azizahtun Naviah (LPPM Universitas Islam Darul 'Ulum Lamongan, 2026)
Sigedang Village has abundant coffee and vegetable agrotourism potential at the foot of Mount Sindoro, but its management has not been optimally integrated. This community service program aims to empower the community, especially the Youth Organization (Karang Taruna), in developing ecotourism through an Asset-Based Community Development (ABCD) approach. The methods used include participatory asset mapping, in-depth interviews, and assistance in digital content creation. The results of the activity show that through an experiential ecotourism strategy, village assets in the form of agricultural activities can be packaged into a systematic